Body mass index and nutritional status in pregnant adolescents that attend the high risk clinic of the Hospital Central Universitario Dr. Antonio Maria Pineda (Boletin Médico de Postgrado, 2020)
Adolescent pregnancy is a public health problem due to its social, health and nutritional consequences for the mother and child. With the goal to evaluate the nutritional status of pregnant adolescents who attended the High Obstetric Risk clinic of the Hospital Central Universitario Dr. Antonio Maria Pineda, a cross-sectional descriptive study was done in 165 pregnant adolescents with an average age of 17.24 ± 1.54 years, 45.4% had anemia and 72.1%    were primiparous. The average age of menarche and sexarquia was 11.66 ± 1.4 years and 15.13 ± 1.83 years, respectively. In regards to nutritional status, 54.5% of adolescents had low weight and 38.7% had normal weight in the first trimester. In the third trimester, 67.2% had normal weight, 17.5% had low weight and 10.3% were overweight. In regards to nutritional status progress, 67.7% of adolescents that were underweight in the first trimester had normal weight in the third trimester and 32.3% continued to have low weight; 79.7% of adolescents with normal weight in the first trimester continued to have normal weight while 18.7% became overweight and 1.5% obese. These results show that anthropometric control is necessary in order to nutritionally monitor pregnant adolescents and prevent or control the occurrence of undesirable maternal-fetal conditions.
Keywords: nutritional status; adolescents; pregnancy; body mass index